(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This article explores Robert Louis Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde using Freud’s theories of psychoanalysis to examine the Gothic nature of the novella. Through a three-stage study, the article highlights the manifestation of the unpresentable in the character of Mr. Hyde, who is depicted as the id, a Freudian hypothetical aspect of the human psyche. The article analyzes the different techniques used to create this character and its relation to the representation it stands for. The article argues that the character of Mr. Hyde and its manifestation of the id reveal a deeper understanding of the human psyche, challenging traditional notions of the self and consciousness. The article concludes that The Strange Case of Dr. Jekyll and Mr. Hyde is a prime example of Gothic literature, presenting the unpresentable in a unique and thought-provoking way that calls for a deeper understanding of both the individual and collective identity of the people and the society